INVESTIGATING THE RELATIONSHIP BETWEEN THE COMPONENTS OF PROFESSORS PSYCHOLOGICAL EMPOWERMENT WITH THE ICT PROCESS IN THE CORONAVIRUS CONDITIONS (STUDY SAMPLE IN THE FACULTIES OF PHYSICAL EDUCATION AND SPORTS SCIENCES OF ISLAMIC AZAD UNIVERSITY OF IRAN) - Seyed Vahid Hosseinipour; Vahid Bakhshalipour; Siavash Khodaparast (Sport Scientific And Practical Aspects, 2025)
Background & aim: Educational organizations of the country need changes in empowerment activities of their human resources in accordance with the growth of information and communication technology. The purpose of this study was to Investigating the relationship between the components of professor’ psychological empowerment with the ICT process in the coronavirus conditions in the faculties of physical education and sports sciences of Islamic Azad University of Iran. Methods: This research is applied in terms of purpose and correlational in terms of method and the statistical population is 86 that creates physical education in Islamic Azad University. Standard questionnaires were used. The collected data were analyzed by K-S tests and Pearson Correlation Coefficient, Manova and stepwise using SPSS software were used to analyze the data. Results: The results showed that the correlation between cognitive competence and psychological empowerment was 0.271, functional competence and cognitive empowerment was 0.267, emotional competence and psychological empowerment was 0.063, general skill and psychological empowerment was 0.194 and specialized skill was psychological empowerment. Is 0.201. Statistical results showed that there is a significant relationship between ICT and psychological empowerment in physical education professor (0.001). Conclusion: According to the study findings, information and communication technology can play an important role in sports professor’ empowerment and the use of empowerment training classes are essential to rehabilitate educational centers.